2014
DOI: 10.2174/1386207311301010002
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Algorithm- Back Propagation Artificial Neural Network Model to Quantify the Affinity of Flavonoids Toward P-Glycoprotein

Abstract: Flavonoids, the most diverse class of plant secondary metabolites, exhibit high affinity toward the purified cytosolic NBD2(C-terminal nucleotide-binding domain) of P-glycoprotein (P-gp). To explore the affinity of flavonoids for P-gp, quantitative structure-activity relationships (QSARs) models were developed using back-propagation artificial neural networks (BPANN) and multiple linear regression (MLR). Molecular descriptors were calculated using PaDELDescriptor, and the number of descriptors was then reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Hence, classification of Pgp-interacting compounds is challenging (Wang et al, 2005[ 49 ]) and is a growing research area. Recently, many computational approaches such as quantitative structure activity relationship (Ghandadi et al, 2014[ 13 ]; Palestro et al, 2014[ 30 ]; Shen et al, 2014[ 38 ]), classification models (Adenot and Lahana, 2004[ 2 ]; Chen et al, 2011[ 8 ]; Klepsch et al, 2014[ 17 ]; Levatić et al, 2013[ 23 ]; Li et al, 2014[ 24 ]; Penzotti et al, 2002[ 31 ]; Prachayasittikul et al, 2015[ 34 ]; Wang et al, 2011[ 51 ]), molecular docking (Ghandadi et al, 2014[ 13 ]; Palestro et al, 2014[ 30 ]; Zeino et al, 2014[ 53 ]), and substructure analysis (Prachayasittikul et al, 2016[ 33 ]; Wang et al, 2011[ 51 ]; Klepsch et al, 2014[ 17 ]) have been successfully employed to provide deeper understanding about this promiscuous protein.…”
mentioning
confidence: 99%
“…Hence, classification of Pgp-interacting compounds is challenging (Wang et al, 2005[ 49 ]) and is a growing research area. Recently, many computational approaches such as quantitative structure activity relationship (Ghandadi et al, 2014[ 13 ]; Palestro et al, 2014[ 30 ]; Shen et al, 2014[ 38 ]), classification models (Adenot and Lahana, 2004[ 2 ]; Chen et al, 2011[ 8 ]; Klepsch et al, 2014[ 17 ]; Levatić et al, 2013[ 23 ]; Li et al, 2014[ 24 ]; Penzotti et al, 2002[ 31 ]; Prachayasittikul et al, 2015[ 34 ]; Wang et al, 2011[ 51 ]), molecular docking (Ghandadi et al, 2014[ 13 ]; Palestro et al, 2014[ 30 ]; Zeino et al, 2014[ 53 ]), and substructure analysis (Prachayasittikul et al, 2016[ 33 ]; Wang et al, 2011[ 51 ]; Klepsch et al, 2014[ 17 ]) have been successfully employed to provide deeper understanding about this promiscuous protein.…”
mentioning
confidence: 99%
“…It has been used in engineering and business applications, and is recently also adopted in biomedical research. [18][19][20] Before BPANN analysis, we also applied GA, a stochastic method applying Darwin's evolution hypothesis and used as the variable selection methods optimizing by the crossover and mutation operation. 18,21,22) Using these statistical methods, we finally succeeded in constructing a good model (Q=0.822) according to the classification attained by PCA.…”
Section: Discussionmentioning
confidence: 99%
“…CV values as indicator or even as the ultimate proof of the high predictive power of a QSAR/QSPR model [29]. In recent years, some authors demonstrated that a high value of Q 2 LOO appears to be necessary but not a sufficient condition for the model to have a high predictive power [21,30,31].…”
Section: Many Authors Consider High Qmentioning
confidence: 99%